Reconstructing the Requirements for an Incumbent Candidacy to Achieve Fair dan Democratic Regional Elections: Merekonstruksi Persyaratan Pencalonan Petahana untuk Mewujudkan Pilkada yang Adil dan Demokratis - Fauzia, Ana; Salman, Radian (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Regional elections play a crucial role in democratic governance, ensuring public participation in leadership selection. However, fair electoral competition is often challenged by the undue advantage of incumbent candidates. Specific Background: Indonesia’s Law No. 10 of 2016 permits incumbent regional heads to take a leave of absence during elections rather than resigning, raising concerns about potential abuse of power. Knowledge Gap: While existing studies discuss election regulations, limited research has specifically examined the urgency of mandatory resignation for incumbents seeking re-election. Aims: This study evaluates the fairness of incumbent candidacy requirements and proposes legal reforms to prevent electoral manipulation. Results: The analysis reveals that the leave requirement is insufficient to prevent conflicts of interest, as incumbents retain influence over state resources, policies, and personnel. Comparative legal frameworks from other countries suggest that a resignation mandate can enhance electoral integrity. Novelty: This research uniquely emphasizes the necessity of reconstructing candidacy rules to include mandatory resignation, drawing on constitutional principles of fairness and equality. Implications: The findings advocate for legislative amendments to establish a resignation requirement for incumbents, thereby strengthening democratic processes and ensuring a more equitable electoral system. Highlights: Incumbent Advantage: Allowing leave instead of resignation enables unfair use of state resources. Legal Reform Needed: Mandatory resignation ensures equal competition in elections. Democratic Integrity: Strengthening regulations prevents power abuse and promotes fairness. Keywords: Regional Head, Elections, Incumbent Candidacy, Reconstruction